Peculiarities of sludge formation and composition of oil paraffin carbohydrates in the Upper-Salat deposit; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 2 - Prozorova I. V.; Serebrennikova O. V. Olga Viktorovna; Loskutova Yu. V.; Yudina N. V.; Stakhina L. D.; Nikolaeva Т. L. (Chemistry, 2007)
Заглавие с титульного листа